Mesometanefrico ovary adenocarcinoma type. Report of a case - García La Madrid, Martín (2015)
The literature is reviewed admitting the characteristics of this tumor as primitive mesonephric duct, but its proximity to the ovary will be included in this organ. Histogenetic is analyzed and representative cases of the literature is concerned. We report a single case registered in the No. 2 Central Hospital of the Social Security of Peru in 15 years of existence. Its location was in right ovary with right parametrial invasion and omentum. A month after his speech there recurrent disease with pulmonary metastases and vaginal vault that do not yield to cobalt treatment, chemotherapy or endocrine therapy. Died 5 months after surgery.